Hepatic Metabolomics Analysis of Hybrid Grouper (Epinephelus fuscoguttatus♀×Epinephelus polyphekadion♂) Fed With Quercetin and Sodium Quercetin-5′-Sulfonates - Luo, Jun; Amenyogbe, Eric; Huang, Jian-sheng; Chen, Gang (Frontiers in Marine Science, 2022)
Combining feeding trials and metabolomics analyses of tissues and biofluids could shed light on nutrient effects and changes in feed intake. In the present study, hybrid grouper (F1 hybrid Epinephelus fuscoguttatus♀×Epinephelus polyphekadion♂) was used as the marine fish model to quantify the impacts of quercetin and sodium quercetin-5′-sulfonates on serum biochemistry and the status of hepatic lipid accumulation and the changes of metabolites in the liver using ultra-performance liquid chromatography-electrospray triple quadrupole mass spectrometry (UPLC-QTRAP/MS/MS). The study shows that total protein, albumin, alkaline phosphatase and glucose were not significantly different among the three groups (P > 0.05). Total cholesterol, triglyceride, and alanine aminotransferase of fish fed quercetin, and sodium quercetin-5′-sulfonates were significantly lower than fish fed without additives (P < 0.05). Low-density lipoprotein cholesterol and aspartate aminotransferase of fish fed quercetin were significantly lower than that of fish fed without additives and sodium quercetin-5′-sulfonates (P < 0.05). The high-density lipoprotein cholesterol of fish fed quercetin, and sodium quercetin-5′-sulfonates were significantly higher than that of fish fed without additives (P < 0.05). Lipid accumulation in the quercetin and sodium quercetin-5′-sulfonates groups decreased significantly. Quercetin and sodium quercetin-5′-sulfonates were effective by increasing hypolipidemic and hepatoprotective compounds that are known for reducing blood lipid levels and liver fat accumulation. As a result of this study, we provide international data for metabolic adaptations during the additives feeding using the fish liver as the study model. By understanding the metabolic effects of these feed additives, this study provides a first step toward understanding the molecular mechanisms of these additives and how they function.